Better winding up: A proposal for improved winding up of executory contracts - Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2015)
An evaluation problem exists when winding up executory contracts in case of insolvency. The trustee has difficulties in accurately considering the claim for damages that arises if he chooses to reject a contract instead of accepting it. An unequal treatment of creditors and inefficiencies follow. However, a simple reform can solve this problem. If an executory contract is accepted by the trustee, there should be the same claim for damages as if it had been rejected. Only the difference between this claim for damages and the initial claim should be paid directly out of the estate. – – Bei der Abwicklung schwebender Verträge in der Insolvenz gibt es ein Bewertungsproblem. Der Insolvenzverwalter hat bei der Wahl zwischen der Annahme und Ablehnung eines Vertrages Schwierigkeiten, den durch Vertragsablehnung entstehenden Schadenersatzanspruch richtig zu berücksichtigen. Es kommt zu einer ungleichen Behandlung von Gläubigern und ineffizienten Ergebnissen. Das Problem lässt sich durch eine einfache Reform beheben. Bei Wahl der Vertragserfüllung sollte derselbe Schadenersatzanspruch wie bei Ablehnung bestehen und nur seine Differenz zur vollständigen Erfüllung aus der Masse bezahlt werden müssen.
Keywords: G33; K39; K35; K22; 650